ANALISIS KESEMPATAN KERJA SEKTOR PERTANIAN DI PROVINSI SULAWESI TENGAH - Suwardi, Mohammad (Katalogis, 2016)
The aim of this research is to analyze: (1) the contribution of agriculture sector in the next five years (2015 - 2019) in Central Sulawesi, (2) the elasticity of employment chance of agricultural sector in the province of Central Sulawesi, and (3) the number of employment chance in agriculture sector in the next five years (2015 - 2019 year) in Central Sulawesi province. This research uses literature approach that collects theories related to the aspects researched, obtained from textbooks, journals and previous studies. The results show (1) Averagely, the PDRB contribution of Agriculture Sector in 2015-2019 was 65.57% higher than the average PDRB contribution in Agriculture Sector 2000 to 2014 (59.04%). This shows that the agricultural sector needs special attention in order to improve the economy in Central Sulawesi, (2)Â  Employment Chance Elasticity in Agricultural Sector in Central Sulawesi Province is 0.1513. As the elasticity is between 0 and 1, the positive employment growth rate and the rate of productivity growth is also positive and (3) the rate of employment chance increase rate for the agricultural sector is 0.94% per year. The amount of agricultural employment of 2015 to the 2019 in Central Sulawesi province is 2,109,834 inhabitants. In 2015 - 2019, expansion of employment opportunities in Central Sulawesi is still occupied by the agricultural sector, so that for the next five years the estimation of number of agricultural sector reaches 2,109,834 inhabitants. The number of job opportunities increases or the inclination is positive (Positive Trend).